Molecular imaging of inflammation with PET in acute and ventilator-induced lung injury - Musch, Guido (Frontiers in Physiology, 2023)
This review focuses on methods to image acute lung inflammation with Positron Emission Tomography (PET). Four approaches are discussed that differ for biologic function of the PET reporter probe, radiotracer employed, and the specific aspect of the inflammatory response that is targeted. 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG) is an enzyme substrate whose uptake is used to measure the metabolic activation of inflammatory cells during acute lung injury in the noncancerous lung. H215O and radiolabeled plasma proteins are inert molecules with the same physical characteristics as their nonradioactive counterparts and are used to measure edema and vascular permeability. Tagged enzyme or receptor inhibitors are used to probe expression of these targets induced by inflammatory stimuli. Lastly, cell-specific tracers are being developed to differentiate the cell types that contribute to the inflammatory response. Taken together, these methods cast PET imaging as a versatile and quantitative tool to measure inflammation in vivo noninvasively during acute and ventilator-induced lung injury.